The Conduct of International Economic Relations in the Bush Administration - Heiman, Bruce J. (Tufts Archival Research Center, 2005)
Volume 13, Issue 1. Winter The United States adopted the "open door" policy one hundred years ago. Today, the appointment of James Baker as Secretary of State highlights this theme of diplomatic emphasis on trade negotiations. Bruce J. Heiman tells us what we might expect in the realm of international economic relations under the new administration, and why.